Pelatihan Untuk Pengajuan Pembiayaan Mudharabah Perbankan Syariah Sebagai Peningkatan Kinerja UMKM - Rizal, Mohammad; Mustapita, Arini Fitria; Kartika Sari, Arista Fauzi (University of Islam Malang, 2020)
Financial management is one of the main aspects for the progress of a company. Accounting is a process or way of producing financial information that can be used to make a decision for its users. Implementation methods of Community Service activities is carried out using presentation methods, tutorial systems, and mentoring. The results of the training and mentoring activities for making Islamic banking mudharabah financing proposal aimed at residents of Malang City Kasin Village who are also perpetrators or owners of MSMEs, have been evaluated based on the response and the results of the practices carried out by the participants and assistance for 3 days. This evaluation of community service activities was carried out through a questionnaire and the results of feedback on questions in the questionnaire relating to training and mentoring materials for making bank credit proposal and the enthusiasm of the participants in each question and answer session. The level of understanding of the participants in understanding the material that has been delivered is grouped on a scale of 71% -80.99%, then the community service activities are declared